2013
DOI: 10.1021/jz401770y
|View full text |Cite
|
Sign up to set email alerts
|

Selenolate-Protected Au38 Nanoclusters: Isolation and Structural Characterization

Abstract: We report the isolation and structural characterization of dodecaneselenolate-protected Au 38 clusters (Au 38 (SeC 12 H 25 ) 24 ). These clusters were synthesized via the reaction of phenylethanethiolate-protected Au 38 clusters (Au 38 (SC 2 H 4 Ph) 24 ) with didodecyldiselenide ((C 12 H 25 Se) 2 ).Characterization of the product by mass spectrometry and thermogravimetric analysis confirmed that highly pure Au 38 (SeC 12 H 25 ) 24 had been obtained. The electronic and geometrical structures, bonding characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 34 publications
10
89
0
Order By: Relevance
“…An understanding of the Au local structure was extended in this work by employing a fourshell EXAFS fit following a previously established fitting approach for Au 25 (SR) 18 NCs [40]. At 50 K, Au-Se and core Au-Au bond distances from EXAFS fitting were consistent with Kurashige et al [68]. The second Au-Au scattering shell indicated that the Au-Au interactions on the surface of the Au 13 core were comparable to the thiolateprotected Au 25 .…”
Section: Metal Dopants In Thiolate-protected Au Ncssupporting
confidence: 64%
See 2 more Smart Citations
“…An understanding of the Au local structure was extended in this work by employing a fourshell EXAFS fit following a previously established fitting approach for Au 25 (SR) 18 NCs [40]. At 50 K, Au-Se and core Au-Au bond distances from EXAFS fitting were consistent with Kurashige et al [68]. The second Au-Au scattering shell indicated that the Au-Au interactions on the surface of the Au 13 core were comparable to the thiolateprotected Au 25 .…”
Section: Metal Dopants In Thiolate-protected Au Ncssupporting
confidence: 64%
“…Au L 3 -edge and Se K-edge XAS results were used to investigate the local structure and temperature-dependent bonding properties of Au 25 (SeR) 18 NCs with the XAS data collected presented in Figure 8. Similar to the dodecanceselenolate-Au 25 and -Au 38 studied by Kurashige et al [68], Au-Se bonding produced a broad scattering feature that partially overlapped with Au-Au scattering. Comparing EXAFS oscillations in the k-space at 50 K (Figure 8, top left), late k-space (8-13 Å -1 ) oscillations were significantly more intense for the selenolateprotected Au 25 , potentially from more tightly ordered Au-Au bonding.…”
Section: Metal Dopants In Thiolate-protected Au Ncssupporting
confidence: 62%
See 1 more Smart Citation
“…Similar results were also obtained for the reaction between Au 24 Pd(SC 2 H 4 Ph) 18 and (C 12 H 25 Se) 2 (Figures 8(b) and S17). The reaction of Au n (SR) m clusters with diselenide is often used for the synthesis of Au n (SeR) m clusters, 56,57 but little is known about its mechanism. As shown in Figure 8 Figure S18).…”
Section: Resultsmentioning
confidence: 99%
“…1,[14][15][16][17][18][19][20] In addition to X-ray crystallography, X-ray absorption fine structure (XAFS) techniques have also been found useful to probe the local environment and electronic properties of Au nanoclusters. 8,17,[21][22][23][24][25][26][27][28] Two of these crystallographically determined systems, the phenylethanethiol-capped Au25(SCH2CH2Ph)18 -system (referred to as Au25), 15 and the mercaptobenzoic acid-capped Au102(MBA)44 (referred to as Au102), 1 exhibit similar surface organization ( Figure 1). In the Au25 system, the phenylethanethiol ligands bind to surface gold atoms and form six "double-staples" surrounding a 13-atom icosahedral core, stabilizing the cluster.…”
Section: Introductionmentioning
confidence: 99%